A case study of cesium sorption onto concrete materials and evaluation of wash agents: Implications for wide area recovery. Issue 3 (June 2019) - Kaminski, Michael D.; Mertz, Carol J.; Jerden, James; Kalensky, Michael; Kivenas, Nadia; Magnuson, Matthew
Abstract: To support the viability of a wash-down approach to mitigating nuclear contamination, this study presents a characterization of the aggregate of a common concrete by optical microscopy and the sorption-desorption characteristics of cesium from these into potential wash solutions. Various minerals with weathered surfaces displayed strong affinity for 137 Cs with an effective partition coefficient Kd  = 120 mL/g for micas, >25–90 mL/g for feldspars, and >25–30 mL/g for amphiboles. The desorption Kd into 0.1 M NH4 Cl varied greatly but for amphiboles, sandstones, granite, and fine-grained quartzite it was >200 mL/g as a result of irreversible sorption. These same mineral phases are prevalent in all types of building materials, extending our conclusions more broadly to the problem of wide-area urban decontamination. In contrast, ionic solutions desorbed up to 98% of 137 Cs from cement, suggesting that fresh concretes with an intact surface layer of cement could be more easily decontaminated if Cs + interactions with the underlying minerals could be avoided. For practical applications common, non-hazardous chemicals such as sodium, potassium, and ammonium salts are as effective or more effective than harsher chemicals and expensive chelating agents. For example, when treated shortly after exposure, on time-scales commensurate with early response phase activities, 0.5 M KCl could remove nearly 50% of bound 137 Cs from concrete aggregate. Statistical analyses showed that desorption from the fine aggregate benefited from higher K + and NH4 + concentrations. These results suggest that contamination in large areas of the urban environment can be dramatically reduced using common chemicals obtained readily from local stores.